Case report: Isolated brainstem-cerebellar symptoms in a patient with anti-NMDA receptor encephalitis - Xu, Yongfeng; Tao, Qingqing; Dong, Yi; Zhang, Yinxi (Frontiers in Immunology, 2024)
Cerebellar ataxia is an uncommon and atypical manifestation of anti-N-methyl-D-aspartate receptor (NMDAR) encephalitis, often accompanied by seizures, psychiatric symptoms, and cognitive deficits. Previous cases of isolated brainstem-cerebellar symptoms in patients with anti-NMDAR encephalitis have not been documented. This report presents a case of anti-NMDAR encephalitis in which the patient exhibited cerebellar ataxia, nystagmus, diplopia, positive bilateral pathological signs, and hemiparesthesia with no other accompanying symptoms or signs. The presence of positive CSF anti-NMDAR antibodies further supports the diagnosis. Other autoantibodies were excluded through the use of cell-based assays. Immunotherapy was subsequently administered, leading to a gradual recovery of the patient.